Incidence of Powdery Mildew on Cucurbit Plants and its Ecofriendly Management - Chavan2, Vasant P. Pawar1* and Ashok M. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">Present paper deals with the study of powdery mildew incidence on different cucurbits hosts in different seasons and its biocontrol. In Kharif season Sphaerotheca fuliginea was dominantly present on Cucurbita maxima, Lageneria siceraria and Cucurbita pepo, where as Erysiphe cichoracearum noted on Citrullus lanatus was not reported in 2005 and 2006.Cucurbita maxima, Lageneria siceraria, Luffa acutangula and Luffa cylindrica showed maximum occurrence of Sphaerotheca fuliginea in the rabbi season. Incidence of powdery mildew was mainly reported on the mature leaves followed by stem. Where as in some cases it was reported on tendril, flower and fruit. Dominant association of powdery mildew was mainly reported on basal leaf. However the incidence of powdery mildew was less on the younger leaves of cucurbits. Incidence of powdery mildew is more at post flowering and fruiting stage. However powdery mildew also reported at seedling stage of Cucurbita pepo and Cucurbita maxima. Neem leaf extract at15% concentration, Parthenium leaf at 10% concentrations. Ocimum leaf at 20% concentration, Citrus leaf at 20% concentration, Annona squamosa leaf at 10% concentration, Ipomea at 15% and Jowar leaf at 20% control the powdery mildew of cucurbits. Cow urine at 15% concentration proved to be effective to control powdery mildew on cucurbit. 20% to 25% of Butter milk spray successfully controlled the powdery mildew of cucurbit. Similarly 20% ash spray also found to be successful to control the growth of powdery mildew of cucurbits. Spray of Dashparni ark, a bi-product of plant and animal at 10% concentration inhibited the growth of Erysiphe cichoracearum and Sphaerotheca fuliginea. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">--- 1Department of Botany, ARTS and science college, Bhalod, tq. Yawal, Dist. Jalgaon (M.S.), India 2Seed Pathology and Fungal Biotechnology Laboratory, Department of Botany, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad- 431004 (M.S.), India --- Please Cite This Article As: Vasant P. Pawar and Ashok M. Chavan. 2010. Incidence of Powdery Mildew on Cucurbit Plants and its Ecofriendly Management. J. Ecobiotechnol. 2(6):29-43.